Ukrainian prisoners and community reentry challenges: implications for transitional care - Morozova, Olga (2013)
PURPOSE: The study aims to assess reentry challenges faced by Ukrainian prisoners and to determine the factors associated with having a greater number of challenges in order to suggest pre- and post-release interventions with the aim of facilitating community reintegration. DESIGN/METHODOLOGY/APPROACH: A representative national cross-sectional study with a sample size of 402 prisoners was conducted among imprisoned adults within six months of release. The study consisted of interviews and biological testing for infectious diseases. Anticipated reentry challenges were assessed using a structured questionnaire. FINDINGS: The most difficult and relatively important challenges identified were finding a job or a stable source of income and staying out of prison following release. Risk-specific challenges pertinent to drug users and HIV-infected individuals were assessed as difficult, but generally less important. Similarly, challenges associated with reducing drug relapse were ranked as less important, with only 0.6 percent identifying opioid substitution therapy as a helpful measure. In the multivariate analysis, having a greater number of challenges is associated with previous incarcerations, drug use immediately before incarceration and lower levels of social support. PRACTICAL IMPLICATIONS: To facilitate community re-integration, it is vital to design interventions aimed at reducing recidivism and improvement of social support through comprehensive case management as well as to improve understanding about and address drug dependence issues among inmates by implementing evidence-based treatment both within prisons and after release. ORIGINALITY/VALUE: This is the first comprehensive assessment of community reentry challenges by prisoners in the former Soviet Union.